Antimicrobial Sensitivity Pattern Of Commonly Used Antibiotics Among Adult Enteric Fever Patients (Journal of Preventive and Social Medicine, 2024)
Background: Enteric fever which is a very common bacterial infection in the Bangladeshi population is most commonly acquired by ingestion of water and food contaminated with feces or urine of carriers. Drug resistance in typhoid fever is considered one of the important factors in the morbidity and mortality of the disease. The emergence of strains of Salmonella Typhi resistant to multiple antibiotics poses a serious problem. The increasing frequency of antibiotic resistance has been reported from all parts of the world, but more so from developing countries. Thus this study aim to assess the antimicrobial sensitivity pattern of commonly used antibiotics among adult enteric fever patients.Methods: This cross-sectional comparative study was conducted in the Department of Medicine of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2015 to December 2015. In total 150 individuals were included in this study as the study subjects who were divided into two groups. In Group A, a total of 50 confirmed enteric fever cases and in Group B, a total of 100 non-enteric febrile adult patients were included. A non-probability purposive sampling technique was used in sample collection. All data were processed, analyzed and disseminated by using the MS Office program. For this analysis to fulfill the objective of this study, mainly data from 50 confirmed enteric fever cases were considered.Results: In this study, among the total of our 50 enteric fever cases with isolated salmonellae organisms including S. typhi and S. Paratyphi, during the treatment procedure, as the antibiotics cefepime, cefixime, ceftazidime, ciprofloxacin, imipenem, meropenem and ofloxacin showed 100% sensitivities. Besides ceftriaxone, cotrimoxazole, chloramphenicol and azithromycin showed 98%, 68%, 66% and 54% sensitivities respectively (>50%). On the other hand, more than 50% of resistant cases were found in treatment by nalidixic acid (76%), ampicillin (98%) and amoxicillin (98%).Conclusion: Till today, considering the lower treatment cost and better patient compliance ciprofloxacin may be considered as the drug of choice in treating adult enteric fever patients. Besides cefepime, cefixime, ceftazidime, ciprofloxacin, imipenem, meropenem or ofloxacin can be used in such cases confidently.JOPSOM 2021; 41(2):43-49